2007
DOI: 10.1007/s10549-007-9524-9
|View full text |Cite
|
Sign up to set email alerts
|

Intake of fruits, and vegetables in relation to breast cancer risk by hormone receptor status

Abstract: The inconsistent associations between fruit and vegetable intake and breast cancer risk may be due to heterogeneity of associations by estrogen (ER) and progesterone receptor (PR) status of the tumors. We evaluated this hypothesis in a large (2,386 cases and 2,503 controls) population-based case-control study in Poland, conducted between 2000 and 2003. We observed significant associations between reduced overall risk of breast cancer and increasing levels of total fruit intake (odds ratio (OR) for highest vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
(18 reference statements)
2
13
0
1
Order By: Relevance
“…Our findings are consistent with several previous studies and support the hypothesis that a greater intake of raw vegetables and fresh fruits is associated with a lower breast cancer (La Vecchia et al, 1987;Iscovich et al, 1989;Pawlega 1992;Freudenheim et al, 1996;Hirose et al, 2007;Lisowska et al, 2008;Cottet et al, 2009;Wu et al, 2009;Butler et al, 2010;Sangrajrang et al, 2013). For example, Freudenheim et al (1996) presented a strong significant reduction of the risk for vegetable intake (OR=0.46, 95%CI=0.28-0.74, p<0.001) and non-significant reduction (OR=0.67, 95%CI=0.42-1.09) for fruits intake, for the highest quartile of intake versus the lowest quartile.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with several previous studies and support the hypothesis that a greater intake of raw vegetables and fresh fruits is associated with a lower breast cancer (La Vecchia et al, 1987;Iscovich et al, 1989;Pawlega 1992;Freudenheim et al, 1996;Hirose et al, 2007;Lisowska et al, 2008;Cottet et al, 2009;Wu et al, 2009;Butler et al, 2010;Sangrajrang et al, 2013). For example, Freudenheim et al (1996) presented a strong significant reduction of the risk for vegetable intake (OR=0.46, 95%CI=0.28-0.74, p<0.001) and non-significant reduction (OR=0.67, 95%CI=0.42-1.09) for fruits intake, for the highest quartile of intake versus the lowest quartile.…”
Section: Discussionsupporting
confidence: 93%
“…The inverse association between the vegetable-fruitsoy dietary pattern and breast cancer risk, particularly among postmenopausal women, with a dose-dependent trend for decreasing risk (RR=0.70, 95%CI=0.51-0.95) was observed among Singapore Chinese women (Butler et al, 2010). In turn, Lisowska et al (2008) observed reduced risk of breast cancer with increasing levels of total fruit intake among Polish women from Warsaw and Lodz (OR=0.76, 95%CI=0.63-0.91) for the highest versus lowest quartile. Similarly, the study of Zhang et al (2009) found that women in the highest quartile of total vegetable and fruit intake had a 72% and a 47% decreased risk of breast cancer (OR=0.28, 95%CI=0.18-0.43 and OR=0.53, 95%CI=0.34-0.82), respectively.…”
Section: Discussionmentioning
confidence: 94%
“…It has been suggested that associations between dietary consumption and breast cancer risk may depend on menopausal status (9–10) or the ER and PR status of the breast cancer (6, 9). However, results from the few published epidemiologic studies addressing the effects of food groups on breast cancer by ER and PR status have been inconsistent (9, 1118). …”
Section: Introductionmentioning
confidence: 99%
“…A perda de peso per se explicaria apenas em parte esses processos 2 . Outros achados também colocaram em evidência a importância das frutas e hortaliças na alimentação, como fontes de minerais, vitaminas, fibras alimentares, antioxidantes e fitoquímicos, que protegem o organismo contra o envelhecimento precoce, a aterosclerose e alguns tipos de câncer [3][4][5][6][7][8][9] . Mais recentemente, Stephen et al 10 mostraram o papel protetor das frutas e hortaliças contra o tromboembolismo venoso, em estudo prospectivo com duração de 12 anos, em amostra de, aproximadamente, 15 mil pessoas.…”
Section: N T R O D U ç ã Ounclassified